Epigenetic disruption meets immune deficiency: a case report of ICF syndrome linked to DNMT3B mutation - Ali, Zaid Al; Al-Ali, Khaled F.; Bader, Fatima; Alhalabiya, Nancy; Sous, Deema; Abulehia, Ayah (Frontiers in Immunology, 2026)
Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome is a rare, autosomal recessive primary immunodeficiency, with fewer than 120 cases reported worldwide. ICF type 1 (ICF1) is the most prevalent subtype. Despite its rarity, ICF1 presents a distinct set of clinical features that necessitate increased awareness, particularly in populations with high rates of consanguinity. This case presents a two-year-old Palestinian boy born to consanguineous parents who presented with recurrent respiratory tract infections, facial dysmorphisms, and hypogammaglobulinemia. A comprehensive immunologic evaluation confirmed markedly reduced immunoglobulin levels consistent with an antibody deficiency. Genetic testing identified a homozygous missense mutation in DNMT3B (Arg826Cys), establishing the diagnosis. The patient was started on intravenous immunoglobulin (IVIG) replacement therapy, which was well tolerated and led to a noticeable reduction in infection frequency and an overall clinical well-being improvement. While treatment remains supportive, early recognition and immunologic management can significantly reduce morbidity. This case highlights the importance of early diagnosis and immunologic support in ICF1 syndrome, reinforces genotype–phenotype correlations, and provides valuable insights from an underrepresented region to improve global awareness, diagnosis, and care, being only the second genetically confirmed case from Palestine.